Comparative Analysis Of Zakat Management In Improving People's Economy In Indonesia, Sudan, And Jordan - Hakim, Muhammad Luqman El; Nasution, Muhammad Syukri Albani; Batubara, Maryam (UNIVERSITAS PAKUAN, 2025)
This study analyzes the comparison of zakat management in improving the people's economy in Indonesia, Sudan, and Jordan. Zakat is an Islamic financial instrument that plays an important role in poverty alleviation and the improvement of community welfare. However, the implementation and effectiveness of zakat management differ in each country due to regulatory factors, institutional structures, and patterns of zakat collection and distribution. This research uses a descriptive qualitative approach with literature study and comparative analysis methods. Data were collected through semi-structured interviews and literature studies on regulations, policies, and practices of zakat management in the three countries. The research results show that the management of zakat in Indonesia is carried out by the National Zakat Amil Agency (BAZNAS) and Zakat Amil Institutions (LAZ) with a voluntary collection model. In Sudan, zakat is managed by the Diwan al-Zakat with a mandatory collection system, whereas in Jordan, zakat is under the management of the Sunduq al-Zakat, supervised by the Ministry of Awqaf, with a variety of more diverse social programs. The comparison shows that although the three countries have the same goal of supporting the people's economy, differences in regulations and management models affect the effectiveness of zakat distribution. This study recommends the optimization of zakat digitalization systems, increased transparency, and strengthened regulations so that zakat can contribute more significantly to the economic empowerment of the community.